sqrt(12-4x)-x=0

Simple and best practice solution for sqrt(12-4x)-x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for sqrt(12-4x)-x=0 equation:


Simplifying
sqrt(12 + -4x) + -1x = 0
(12 * qrst + -4x * qrst) + -1x = 0
(12qrst + -4qrstx) + -1x = 0

Solving
12qrst + -4qrstx + -1x = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add 'x' to each side of the equation.
12qrst + -4qrstx + -1x + x = 0 + x

Combine like terms: -1x + x = 0
12qrst + -4qrstx + 0 = 0 + x
12qrst + -4qrstx = 0 + x
Remove the zero:
12qrst + -4qrstx = x

Combine like terms: x + -1x = 0
12qrst + -4qrstx + -1x = 0

The solution to this equation could not be determined.

See similar equations:

| 9x-21=7x+10 | | 5-2=1/7y-8 | | 3x=-21^1/2 | | 7x^2+4=2 | | 35/99=5/9g | | 8x+9-12x=4x-13-5y | | N*4=15-N | | 6.9x-1.6=12.2 | | 1/4×1/4÷1/4 | | 4/3x-8=0 | | A^2-2a+6=-7a | | 5(6z-1)-2(z+3)=20(z+1) | | 1/4×1/4×1/4 | | 5+9(x-3)=8-7(x-2) | | (x-y)(xr-xs-ys+yt)=(x+y)(p-q) | | 4x-5y+7z=2 | | 20-14=u | | 5/1x=6/5 | | y=-6/2=1 | | 14x^2/14x | | 2x^2-70x+600=0 | | 16x+43-39x=11 | | 7=2+g | | (x+1)(x-i)(x+i)=0 | | 2-2y=-8x | | 8+2x+3-x=2x+4 | | (12+X)X=36 | | (x-5)(xi)(x+i)=0 | | 8(2)+y=7 | | 4m^3-24m^2+100m= | | A^2-28=3a | | 15*.6=.7x+.4y |

Equations solver categories